Riociguat for the treatment of chronic thromboembolic pulmonary hypertension: a long-term extension study (CHEST-2) - Simonneau, Gérald; D'Armini, Andrea M; Ghofrani, Hossein-Ardeschir; Grimminger, Friedrich; Hoeper, Marius M; Jansa, Pavel; Kim, Nick H; Wang, Chen; Wilkins, Martin R; Fritsch, Arno; Davie, Neil; Colorado, Pablo; et al. (The European respiratory journal, 2015)
Riociguat is a soluble guanylate cyclase stimulator approved for the treatment of inoperable and persistent/recurrent chronic thromboembolic pulmonary hypertension (CTEPH). In the 16-week CHEST-1 study, riociguat showed a favourable benefit-risk profile and improved several clinically relevant end-points in patients with CTEPH. The CHEST-2 open-label extension evaluated the long-term safety and efficacy of riociguat. Eligible patients from CHEST-1 received riociguat individually adjusted up to a maximum dose of 2.5 mg three times daily. The primary objective was the safety and tolerability of riociguat; exploratory efficacy end-points included 6-min walking distance (6MWD) and World Health Organization (WHO) functional class (FC). Overall, 237 patients entered CHEST-2 and 211 (89%) were ongoing at this interim analysis (March 2013). The safety profile of riociguat in CHEST-2 was similar to CHEST-1, with no new safety signals. Improvements in 6MWD and WHO FC observed in CHEST-1 persisted for up to 1 year in CHEST-2. In the observed population at 1 year, mean±sd 6MWD had changed by +51±62 m (n=172) versus CHEST-1 baseline (n=237), and WHO FC had improved/stabilised/worsened in 47/50/3% of patients (n=176) versus CHEST-1 baseline (n=236). Long-term riociguat had a favourable benefit-risk profile and apparently showed sustained benefits in exercise and functional capacity for up to 1 year.
Keywords: pyrazoly; zátěžový test; respirační funkční testy; Humans; Risk; riziko; lidé středního věku; pyrimidiny; guanylátcyklasa; Double-Blind Method; Drug Administration Schedule; Dose-Response Relationship, Drug; Female; Aged; Antihypertensive Agents; senioři; dvojitá slepá metoda; lidé; Respiratory Function Tests; Hypertension, Pulmonary; Exercise Test; časové faktory; chůze; plicní hypertenze; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Thromboembolism; Walking; tromboembolie; vztah mezi dávkou a účinkem léčiva; Pyrimidines; antihypertenziva; mužské pohlaví; Pyrazoles; Time Factors; rozvrh dávkování léků; následné studie; Guanylate Cyclase